Panel Session-Co-creative Virtual Reality Content Development in Healthcare: Tackling The Content Availability Problem - Antoniou, Panagiotis E.; Konstantinidis, Stathis Th; Bamidis, Panagiotis D. (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
Virtual Reality (VR), blanket term used for all the reality-virtuality spectrum, is exploding in proliferation, especially in healthcare. The core challenge of this explosion is the timely and cost-effective provision of bespoke content. Co-creative approaches can facilitate this endeavor by making the educators active participants in the development process reducing development overheads and democratizing healthcare digital content creation. This panel session aims at health educators, VR technologists, developers and technology enthusiasts. It will present, and actively engage its audience with co-creative methods and approaches, providing them with the gateway experience that could become useful for introducing such methods in their institutions and workflows. The panelists are cross-disciplined educational technologists/medical educators with extensive experience in the field of technology enhanced learning (TEL) who have implemented such methodologies in practice. The workshop will follow a mixed format. A brief "observations from the field" introduction to the topics of VR TEL and co-creation will be followed by an introduction to real world healthcare VR projects and resources. In these, realistic examples, the participants will engage in hands-on storyboarding and non-technical design and development tasks, in order to acclimate with the co-creative process and become able to explore it for their own use cases.